Asymmetries in the Southern Ocean contribution to global heat and carbon uptake ... - Roussenov, Vassil; Williams, Richard G.; Meijers, Andrew J.S.; Katavouta, Anna; Ceppi, Paulo; Rosser, Jonathan P.; Salvi, Pietro (Zenodo, 2024)
Supporting data files in Heat_Carbon_diag_CMIP6.tar.gz, NetCDF format : (1) Carbon diagnostics Ocean carbon storage (Cstorage) and uptake (Cuptake) for each model time series of the global, north of 30N, south of 30S; four scenarios: historical, historical with GHG, historical with aerosols, SSP2-4.5 Ocean_Cstorage_CMIP6_historical.nc Ocean_Cstorage_CMIP6_historical_greenhouse_gases.nc Ocean_Cstorage_CMIP6_historical_only_aerosols.nc Ocean_Cstorage_CMIP6_ssp245.nc Ocean_Cuptake_CMIP6_historical.nc Ocean_Cuptake_CMIP6_historical_greenhouse_gases.nc Ocean_Cuptake_CMIP6_historical_only_aerosols.nc Ocean_Cuptake_CMIP6_ssp245.nc Contributions of Southern Ocean (frac_SO) and northern ocean (frac_NO) carbon uptake to global carbon uptake, model mean and STD frac_Carb_hist-GHG.nc frac_Carb_historical.nc frac_Carb_ssp245.nc Carbon flux into the ocean, model mean and STD 2D fields for all 4 scenarios Carbon_flux_Figure3_UPD.nc (2) Heat diagnostics at the Top of the Atmosphere (TOA) TOA heat uptake (N) and radiative ...